Role of fibronectin in Pneumocystis carinii attachment to cultured lung cells. - Pottratz, S T (1990)
Attachment of pathogens to host cells is a prerequisite for the development of many infections. Pneumocystis carinii (PC) pneumonia is characterized by attachment of PC trophozoites to the alveolar epithelium. The mechanism of this process is unknown. Fibronectin (Fn) is a glycoprotein present in the alveolar space known to mediate cell-cell attachment, including the attachment of certain pathogens to host epithelial cells. In this study the binding of Fn to PC trophozoites has been characterized in vitro using 125I-Fn. Fn binds saturably and specifically to 6.4 x 10(5) binding sites per organism with an apparent binding constant, Kd, of 1.2 x 10(-8) M. Fn binding to PC was inhibited by the addition of Arg-Gly-Asp-Ser (RGDS), a tetrapeptide containing the active site of the cell-binding domain of Fn. PC attachment to an alveolar epithelial cell line was quantified using 51Cr-labeled PC trophozoites. Attachment was decreased from 24 +/- 1.9% to 12.1 +/- 1% (P less than 0.01) by the addition of an anti-Fn antibody, an effect that could be overcome by the addition of excess free Fn. It is concluded that binding of Fn to PC may be an important initial step in the attachment of the organism to alveolar epithelial cells. Furthermore, it appears that PC recognizes and binds to the RGDS cell attachment site of Fn.